2000
DOI: 10.1038/sj.onc.1203142
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of p53-mediated suppression of homologous recombination from G1/S cell cycle checkpoint control

Abstract: The tumor suppressor p53 is considered as the guardian of the genome which is activated following genotoxic stress. In many cell types, p53 mediates G1 cell cycle arrest as the predominant cellular response. Inactivation of wild-type p53 leads to loss of G1/S checkpoint control and to genomic instability, including increased spontaneous homologous recombination (HR). To determine whether regulation of the G1/S checkpoint is required for suppression of HR, we assessed recombination events using a plasmid substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
98
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 50 publications
7
98
1
2
Order By: Relevance
“…This strongly indicates a direct rather than a transcriptiondependent action of p53 during recombination. This is in line with earlier reports on the separation of transcriptional, growth regulatory and apoptotic activities of p53 from recombination regulation (Saintigny et al, 1999;Dudenho¨ffer et al, 1999;Willers et al, 2000;Akyu¨z et al, 2002). Data from in vivo models for transcriptionally inactive p53 indicated the existence of an unidentified activity counteracting cancerogenesis (Komarov et al, 1999;Jimenez et al, 2000).…”
Section: Indications For An Antagonistic Role Of P53 During Replicatisupporting
confidence: 80%
See 1 more Smart Citation
“…This strongly indicates a direct rather than a transcriptiondependent action of p53 during recombination. This is in line with earlier reports on the separation of transcriptional, growth regulatory and apoptotic activities of p53 from recombination regulation (Saintigny et al, 1999;Dudenho¨ffer et al, 1999;Willers et al, 2000;Akyu¨z et al, 2002). Data from in vivo models for transcriptionally inactive p53 indicated the existence of an unidentified activity counteracting cancerogenesis (Komarov et al, 1999;Jimenez et al, 2000).…”
Section: Indications For An Antagonistic Role Of P53 During Replicatisupporting
confidence: 80%
“…Wild-type p53 (wtp53) stabilizes the genome by G1 arrest and pro-apoptotic functions, thereby giving time to repair and eliminate cells with irrepairable damage, respectively (Levine, 1997). During the last years it was also established that p53 downregulates homologous recombination independently of its transcriptional transactivation and growth regulatory functions (Saintigny et al, 1999;Dudenho¨ffer et al, 1999;Willers et al, 2000). This activity is directed towards gene conversion events, involving short stretches of homologies in particular (Bertrand et al, 1997;Saintigny et al, 1999;Akyu¨z et al, 2002).…”
mentioning
confidence: 99%
“…Intriguingly, p53 protein appears to promote only some DNA damage repair pathways, such as base excision repair, mismatch repair and nucleotide excision repair [9][10][11], but inhibit DNA DSB repair pathways, including the HR, NHEJ and SSA pathways [12][13][14]. It has been demonstrated that p53 exerts a direct effect on DNA DSB repair, as mutations in p53 that impair or even abolish its transcriptional activity and cell cycle regulatory capacity do not significantly affect its inhibition of HR [15][16][17]. Further experiments have shown that the p53 protein is able to interact with repair proteins to prevent repair complex formation, such as RAD51 (a recombinase for HR) and replication protein A (RPA; a single-strand DNA-interacting protein required for stabilizing processed DNA ends) [16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated p53 being an important integral part of these checkpoints (Bargonetti and Manfredi, 2002). Accumulated p53 in response to DNA damage or through experimental overexpression has been shown to cause growth arrest at G1 (Agami and Bernards, 2000;Wesierska-Gadek and Schmid, 2000;Willers et al, 2000) and/or G2 (Agarwal et al, 1995;Taylor et al, 1999;Taylor and Stark, 2001;Nakamura et al, 2002) or to induce apoptosis (Vousden, 2000;Kokontis et al, 2001). In some cases, overexpression of the wt p53 induces cellular senescence (Sugrue et al, 1997;Dubrez et al, 2001;Jung et al, 2001).…”
Section: Introductionmentioning
confidence: 99%